2004
DOI: 10.1093/humrep/deh104
|View full text |Cite|
|
Sign up to set email alerts
|

The merits of blastocyst versus cleavage stage embryo transfer: a Cochrane review

Abstract: The current evidence fails to support a widespread change of practice from cleavage stage to blastocyst stage embryo transfer in couples undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 2 publications
0
13
1
Order By: Relevance
“…The advances in culture media over the last decade have made this extended culture possible. An increasing number of studies have confirmed that high implantation rates can be achieved after transfer of blastocysts in various patient populations, but mostly in good-prognosis patients (7). Although the design of newer, sequential media is based on the in vivo environment of the embryos, not every embryo can grow to the blastocyst stage, even when they are derived from excellent-prognosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The advances in culture media over the last decade have made this extended culture possible. An increasing number of studies have confirmed that high implantation rates can be achieved after transfer of blastocysts in various patient populations, but mostly in good-prognosis patients (7). Although the design of newer, sequential media is based on the in vivo environment of the embryos, not every embryo can grow to the blastocyst stage, even when they are derived from excellent-prognosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has not been definitively established that blastocyst transfers result in better fetal outcomes compared with ET on day 3 (8). To address the question of whether it is reasonable to prolong embryo culture to the blastocyst stage, we compared the ongoing PRs in a group of selected patients who were randomly allocated to either SET on day 3 or single blastocyst transfer (SBT).…”
mentioning
confidence: 99%
“…Also, blastocyst culture places more demand on the resources of the laboratory, as the embryos occupy space in the incubators for longer periods of time and require additional handling. Randomized controlled trials involving unselected patients, comparing transfer at the cleavage stage versus at the blastocyst stage, do not suggest that either alternative is superior in terms of births per oocyte pickup (3). Against this background, there seems to be a case for improving the selection of cleavage stage embryos.…”
mentioning
confidence: 99%